Immunomodulatory and anti-inflammatory activity induced by oral administration of a probiotic strain of Lactobacillus casei - Bibas Bonet, María Eugenia (2006)
The aim of this work was to study the effect of the long-term cyclic administration of the probiotic strain of Lactobacillus (L.) casei CRL 431 as a mucosal immunomodulator of the immune cells associated with the lamina propria of the small intestine, bronchus and other immune cells not associated with mucosal tissues, such as peritoneal macrophages. BALB/c mice were orally administered with a suspension of Lc 109 cfu/ day/animal in non-fat milk (NFM) 10% for two consecutive days, the optimal dose selected in previous studies to reach protective immunity. This administration was repeated cyclically every 5 days for 98 days. Mice in the control group received only NFM 10%. Samples were taken after two days of L. casei administration and every 14 days until day 98. The small intestine and lungs were removed for histological slices preparation. Haematoxilin-eosin stains were made for histological studies of the small intestine. The number of IgA producing cells in the lamina propria of the small intestine and in bronchus was determined by immunofluorescence assays. Regulatory (IL-4, IL-10) and proinflammatory (TNF-α, INF-γ) cytokines were measured in the gut. Peritoneal macrophages were collected during the same periods for phagocytosis assays. We determined an increase in the number of IgA+ cells in the lamina propria of the small intestine in all the periods assayed and in BALT only until day 28. The cytokines studied (IL-10, IL-4, TNF-α and INF-γ) increased in most of the periods assayed, the effect being more remarkable for the anti-inflammatory cytokines such as IL-4 and IL-10. INF-γ was also increased but no modifications in the histological studies of the small intestine were observed, suggesting other roles for this cytokine The phagocytic activity of PM increased for most of the periods assayed. We demonstrated that long-term cyclic oral L. casei administration favors mucosal immunity and modulates the immune response to maintain the homeostasis at the mucosal level.